ok so i suck at this even though its simple...i tend to over think these things....your help would be much appreciated

2p-3q=6

-2p+3q=-6

Printable View

- Oct 22nd 2008, 06:28 PMI hate Mathsystem of equations
ok so i suck at this even though its simple...i tend to over think these things....your help would be much appreciated

2p-3q=6

-2p+3q=-6 - Oct 22nd 2008, 06:40 PMWhoaBlackBetty
It is easy, but you need to find either p or q first and use it to solve for the other one. So, if you have

$\displaystyle

2p-3q=6

$

$\displaystyle -2p+3q=-6

$

Say you want P for the first equation so you have to get P on one side alone...

$\displaystyle 2p-3q=6

$

Divide out your 2 to get P alone.

$\displaystyle 2p/2=6/2+3q/2$

Which reduces to p=3+3q/2

Now, you have P so find Q by putting the value of P in the other equation...

$\displaystyle -2(3+3q/2)+3q=-6$ and I think you can figure out the rest. - Oct 22nd 2008, 06:55 PMrunner940
Ok, first you take equation 2 and solve for one of the variables.

Let's solve for 'p'.

-2p+3q=-6

-2p=-3q-6

2p=3q+6

p=3/2q+6/2

p=1.5q+3

Now, take the equation and plug it into the variable of the first equation.

2p-3q=6

2(1.5q+3)-3q=6

Now solve the equation for 'q'.

q=1

Now, plug 'q' into the first equation.

2p-3q=6

2p-3(1)=6

2p-3=6

2p=9

p=4.5

Plug in 'p' and 'q' to check you answers in a equation (it doesn't matter if its the ist or second equation.)

Let's use the first since it look the easiest.

2p-3q=6

2(4.5)-3(1)=6 ?

9-3=6 ?

6=6

The answers are equal so you know your answers work.

Hope this helps.(Rofl)